PHYSICOCHEMICAL CHARACTERIZATION, BIOACTIVITY, AND ACARICIDAL POTENTIAL OF ESSENTIAL OILS FROM Cymbopogon citratus AND Citrus sinensis PEEL AGAINST ADULT Amblyomma variegatum - Owolabi, Yetunde Hannah; George, Butcher Danladi Jonathan; Natala, Audu Joseph; Umar, Mohammed Bello (FUDMA Journal of Sciences, 2026)
The increasing resistance of ticks to synthetic acaricides has driven interest in plant-derived alternatives. This study evaluated the extraction yield, physicochemical properties, chemical composition and acaricidal efficacy of essential oils from lemongrass (Cymbopogon citratus) and orange peel (Citrus sinensis) against adult Amblyomma variegatum. Essential oils were obtained by hydro distillation and yields were calculated. Physicochemical properties were determined using standard Association of Official Analytical Chemists methods, while chemical composition was analyzed using gas chromatography–mass spectrometry. Acaricidal activity was assessed using the Adult Immersion Test at concentrations of 10%, 20%, and 30%, with mortality recorded at 24, 48, and 72 hours post-treatment. Amitraz (0.1%) served as the positive control, while extra-virgin olive oil was used as diluent and negative control. Lemongrass oil yielded 0.70% (2.0 g), whereas orange peel oil yielded 4.70% (14.0 g). GC-MS analysis identified citral (71.0%) as the major component in lemongrass oil and limonene (36.0%) in orange peel oil. Both oils exhibited concentration- and time-dependent acaricidal activity. At 30% concentration after 72 hours, mortality rates of 73.33% and 60.00% were recorded for lemongrass and orange peel oils, respectively. Although neither treatment achieved complete mortality comparable to amitraz, lemongrass oil consistently demonstrated greater efficacy. These findings indicate that both essential oils possess significant acaricidal potential with lemongrass oil showing superior activity. Their effectiveness at higher concentrations supports their potential as environmentally friendly alternatives for integration into tick management strategies.